(untitled) (Actual Problems of Psychology in Educational Institutions, 2018)
The article analyzes the development of ideas on the problem of deviations in the Republic of Belarus. The approaches and principles used in the process of solving problems in this problem area are considered. The main hypotheses are presented, and also the complex of problems on the declared problem is defined and systematized.